N- and O-Trideuteromethylation of Drugs and Intermediates with Trimethyloxosulphonium Iodide-d9 Enabled by a Mechanochemical Synthesis - Dharmik, Pranal M.; Detke, Sandip J.; Harasure, Omkar C.; Kharkar, Prashant S. (Sustainability & Circularity NOW, 2025)
Solvent-free, sustainable organic synthetic approaches based on the use of microwaves, ultrasound, or mechanochemistry are needed from a green chemistry perspective. Mechanochemical synthesis involves the coupling of mechanical and chemical processes at the molecular level. In the present study, we have applied mechanochemistry for the deuteration of drugs and intermediates, particularly N- and O-trideuteromethylation. Conventionally, MeI-d3, a carcinogenic and relatively expensive reagent, is used for introducing a trideuteromethyl (–OCD3) group in drugs/intermediates. Here, the utility of trimethyloxosulphonium iodide-d9 (TDMSOI) was investigated as the –OCD3 source, for developing and optimizing a novel, one-pot, solvent-free, mechanochemical method for N- and O-trideuteromethylation of several drugs/intermediates with appreciable degree of deuteration (~90% D), particularly those containing phenol, acid, and amine functional groups. The investigated method is scalable and is of potential interest to the Medicinal Chemistry and Drug Discovery community, given the perceived importance of deuteration as a viable strategy for affecting the in vivo half-life of drugs.
Keywords: Deuterated drugs; Solvent-free synthesis; Mechanochemistry; Green synthesis; Trideuteromethylation